(untitled) (Global Journal of Management and Business Research, 2021)
This aim of this study is to investigate the financial performance among the selected cement companies of Bangladesh. This study also includes comparative performance evaluation through financial ratio analysis. This study is based on five leading cement companies, which are Aramit Cement Ltd., Confidence Cement Ltd., Heidelberg Cement Ltd., Premier Cement Ltd., and Crown Cement Ltd. This research is based upon five years of analysis, from 2015 to 2019, and carried by secondary information, and to produce ratio analysis, data has been taken from annual reports, articles, and publications, etc. This study reveals the financial position of selected cement companies which is very important for the industry because of its growth and role in development. Financial Ratios such as Current Ratio, Return on Assets (ROA),Return on Equity (ROE),Net Profit Margin, inventory Turnover Ratio, Total Asset Turnover Ratio , Earnings per share , Debt to Equity Ratio were used for comparing performance of these cement companies.